Laparoscopic hepatectomy is a feasible and safe choice for primary hepatocellular carcinoma located at favorable location during the development period of a tertiary hospital: A case–control study - Yi-Hsuan Lee; Yu-Ting Huang; Tsai-Ling Kuo; Ming-Che Lee; Yen-Cheng Chen (Tzu Chi Medical Journal)
OBJECTIVES: Laparoscopic hepatectomy (LH) for hepatocellular carcinoma (HCC) has been well known for its advantages in the past 10 years, but little is known regarding its oncologic outcomes while the technique is being developed at an institution. This study aimed to evaluate the safety and effectiveness of LH for patients with primary HCC at favorable locations, focusing on postoperative short- and long-term outcomes during the development period. MATERIALS AND METHODS: We retrospectively reviewed patients diagnosed with primary HCC who underwent hepatectomy between January 2013 and December 2019 at Hualien Tzu Chi Hospital. Patients with HCC at favorable locations (anterolateral segments) were collected and divided into laparoscopic and open hepatectomy (OH) groups. The data for long-term outcomes, as the primary endpoint, and postoperative outcomes, as the secondary endpoint, were collected. Results: The review included 159 patients, among which 42 and 44 patients in favorable locations underwent open and laparoscopic hepatectomies, respectively. There were no significant differences in intraoperative blood loss, major complication rate, and 90-day mortality rate between the two groups. The laparoscopic group had a lower transfusion rate, shorter postoperative hospital stay, and lower 90-day readmission rate. There were no significant differences in 12-, 36-, and 60-month overall survival and disease-free survival. Conclusion: LH for favorably located HCC is the preferred surgical approach compared to OH due to the decreased transfusion rate, shorter postoperative hospital stay, and lower 90-day readmission rate. LH did not compromise the 90-day mortality rate with sustained long-term overall and disease-free survival. LH for favorably located HCC is a safe and effective surgical approach even during the development period.